PENGARUH PRODUK DOMESTIK BRUTO, NILAI TUKAR RUPIAH, DAN IMBAL HASIL SUKUK, TERHADAP PERTUMBUHAN SUKUK KORPORASI OUTSTANDING INDONESIA PERIODE SEMESTER I TAHUN 2011 – PERIODE SEMESTER II TAHUN 2019 - Puspita, Andani; Anthony, Mayes; Rahmat, Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine how much influence the Gross Domestic Product, Rupiah Exchange Rate Against US Dollar, and Sukuk Yields on the Growth of Outstanding Indonesia Corporation's Sukuk for the first semester of 2011 - the second semester of 2019. This study uses independent variables consisting of Gross Domestic Product, Rupiah Exchange Rate Against US Dollar, and yield on Sukuk, as well as the dependent variable which is the Growth of Outstanding Indonesia Corporation's Sukuk. The data used in this research is the data for the first semester of 2011 - the second semester of 2019. The analysis method used is descriptive quantitative and analyzed partially or simultaneously with multiple linear regression with the OLS (Ordinary Least Square) approach which is processed using E-Views version 10. The test results show that the Gross Domestic Product, Rupiah Exchange Rate Against US Dollar, and the Sukuk Yields simultaneously has a significant effect on the Growth of Outstanding Indonesia Corporation's Sukuk. The Gross Domestic Product has a positive and significant effect on the Growth of Outstanding Indonesia Corporation's Sukuk, the Rupiah Exchange Rate Against US Dollar has a negative and significant effect on the Growth of Outstanding Indonesia Corporation's Sukuk, and the yield on Sukuk has a positive and insignificant effect on the Growth of Outstanding Indonesia Corporation's Sukuk. In addition, the value obtained from the adjusted R2 was 92.21%.Keywords: Gross Domestic Product, Rupiah Exchange Rate Against US Dollar, Sukuk Yields, Growth of Outstanding Indonesia Corporation's Sukuk.